Case series of adenomatoid odontogenic tumour of jaws with variations in presentation. Issue 1 (12th January 2020) - Chugh, Ankita; Srivastava, Isha; Khatana, Shruti; Nalwa, Aasma; Bharti, Jyotsna Naresh
Abstract : Adenomatoid odontogenic tumour (AOT) is a rare tumour of odontogenic origin with distinct clinicopathological appearance but is often clinically misdiagnosed as a cyst. The most common site is the anterior maxilla in the canine region. We present here two cases, one at its commonest location in the maxillary canine while the other is at the uncommon location of the anterior mandible. Its clinical features of painless slow growing swelling, association with impacted tooth and radiographic appearance of well defined predominantly radiolucent lesion are overlapping with other oral pathologies like dentigerous cyst, radicular cyst, calcifying odontogenic cyst, calcifying epithelial odontogenic tumour, unicystic ameloblastoma etc. One must be aware and updated with the variation in appearance of AOT. Encapsulation of tumour causes less cumbersome enucleation of the tumour, a successful treatment as it reduces the chances of recurrence.